Novel chimerized IgA CD20 antibodies: Improving neutrophil activation against CD20-positive malignancies. Issue 1 (1st January 2020) - Evers, Mitchell; Ten Broeke, Toine; Jansen, J.H. Marco; Nederend, Maaike; Hamdan, Firas; Reiding, Karli R.; Meyer, Saskia; Moerer, Petra; Brinkman, Iris; Rösner, Thies; Lebbink, Robert Jan; Valerius, Thomas; et al.
ABSTRACT: Current combination therapies elicit high response rates in B cell malignancies, often using CD20 antibodies as the backbone of therapy. However, many patients eventually relapse or develop progressive disease. Therefore, novel CD20 antibodies combining multiple effector mechanisms were generated. To study whether neutrophil-mediated destruction of B cell malignancies can be added to the arsenal of effector mechanisms, we chimerized a panel of five previously described murine CD20 antibodies to the human IgG1, IgA1 and IgA2 isotype. Of this panel, we assessed in vitro antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC) and direct cell death induction capacity and studied the efficacy in two different in vivo mouse models. IgA antibodies outperformed IgG1 antibodies in neutrophil-mediated killing in vitro, both against CD20-expressing cell lines and primary patient material. In these assays, we observed loss of CD19 with both IgA and IgG antibodies. Therefore, we established a novel method to improve the assessment of B-cell depletion by CD20 antibodies by including CD24 as a stable cell marker. Subsequently, we demonstrated that only IgA antibodies were able to reduce B cell numbers in this context. Additionally, IgA antibodies showed efficacy in both an intraperitoneal tumor model with EL4 cells expressing huCD20 and in an adoptive transfer model with huCD20-expressing B cells. Taken together, we show that IgA, like IgG, can induce ADCC and CDC, but additionally triggers neutrophils to kill (malignant) B cells. We conclude that antibodies of the IgA isotype offer an attractive repertoire of effector mechanisms for the treatment of CD20-expressing malignancies.